Mimbar Dakwah Ke Gelanggang Politik: Konstestasi Otoritas Keagaman Ndoro Habib di Banyuwangi : Konstestasi Otoritas Keagaman Ndoro Habib di Banyuwangi - Syamsul Arifin; Najamudin, Atho’ilah Aly (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
Ndoro Habib in Banyuwangi Regency is a religious figure who attracts attention because of his role as a religious elite who has the authority to form congregations and influence social change. One manifestation of this role is the existence of a taklim assembly led directly by Ndoro Habib. However, since the beginning of 2017, Ndoro Habib's involvement in the political arena has become very massive, as seen from his efforts to reproduce religious discourse that affects the electoral political awareness of his followers, groups and families. This study aims to analyze the dynamics of changes in Ndoro Habib's behavior from the focus of da'wah to political activities. The research uses a qualitative method with a historical ethnographic approach, involving data from 1940 to 2023 collected through interviews and field observations. The results showed three main findings. First, Ndoro Habib's behavioral changes were influenced by the surrounding social conditions. Second, these changes are also driven by power relations that shape adaptation strategies. Third, Ndoro Habib's political involvement is part of an effort to maintain his existence in building religious authority among his followers. This research provides new insights into the interaction between religion and politics, especially in the context of the role of religious elites in the Banyuwangi region.